MANAJEMEN PEMBIMBINGAN USTADZ DALAM MENERAPKAN DISIPLIN SANTRI DI PESANTREN - Hana Fawziyah Ramadhan (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2021)
The Teacher guidance in applying discipline is an important element in Islamic boarding schools. Ustadz is one of the educators who becomes a role model and has a certain personality that includes responsibility, authority, independence and discipline. The application of student discipline is the most effective means to improve noble character in Islamic boarding schools. Guidance in implementing student discipline, all this cannot be separated from the management in it, so that everyone involved in the Islamic boarding school, from Ustadz, students and boarding school caregivers can follow it well. The focus of the problem in this research are: 1) the managerial weakness of the ustadz in applying the discipline of students to improve noble character at the Al-Ihsan Islamic Boarding School Mathla'ul Huda. 2) to describe improvement efforts in implementing student discipline at Al-Ihsan Islamic Boarding School and Mathla'ul Huda Islamic Boarding School. The research objectives in this study are 1) to describe the Ustadz's obstacles in applying student discipline to improve noble character in both Islamic boarding schools. 2) to describe the improvement efforts made by the ustadz in applying the discipline of students to improve noble character in both pesantren. This study uses a qualitative approach with a descriptive method. Data collection techniques used are interviews and observation. The steps in compiling this research by analyzing the data that have been obtained include reducing the data, presenting the data, and verifying the data. The results of this study The results of this study indicate that the management of Ustadz's guidance in the discipline of santri learning is very influential on increasing noble character in Bandung Regency. For this reason, in general, the author recommends for Teacher at Al-Ihsan and Mathla'ul Huda Islamic Boarding Schools to always seek improvements in instilling discipline in students. The distribution of the results of this study is expected to be useful for the two pesantren studied. Noble morality is the main goal in Islamic moral education that is expected from Teacher, one of which is by applying discipline